NEW TOMATO VARIETIES FOR OPEN GROUND DEVELOPED FOR DIETETIC NUTRITION AND STUFFING - I. Y. Kondratieva; M. R. Engalychev (Овощи России, 2016)
New tomato varieties suitable for growing in open area and greenhouses were developed. The cultivar «Sodruzhestvo» with low content of acids, high content of sugars and dry matters is recommended for baby foods and dietetic nutrition. The fruits of cv. «Voskhod of VNIISSOK’s» are red, solids, and suitable for stuffing.